A student-driven multilevel approach for increasing energy sustainability of remote areas in the Emilia Romagna Apennines. Issue 1 (1st November 2022) - Pedrazzi, Simone; Ottani, Filippo; Parenti, Massimiliano; Parmeggiani, Davide; De Luca, Aurora; Silvestro, Martina Grasso; Spartà, Anna; Tavani, Francesco; Fontana, Pietro; Martini, Niccolò; Martire, Mattia; Bertoni, Manuel; et al.
Abstract: This paper is aimed at discussing a series of energy sustainability solutions proposed by a master class of students in environmental engineering using analytical and visual collaborative tools. The activities described are part of the class "Sustainability and renewable sources" at the University of Modena and Reggio Emilia. Six groups of 3-4 students worked on six energy efficiency and sustainability projects chosen from a remote area of the Apennines in Emilia Romagna. The specificity of the case-study framework allowed the implementation of projects where different sustainability aspects are integrated using tools of transitional thinking: agro-food production, use of renewable energy sources, waste management and social integration were considered. Each group identified the key actors for each project, allowing them to approach sustainability from a multilevel perspective. Net Present Value analyses were applied to evaluate economic viability of each project. Photovoltaic power plants and boilers fueled with local wood are the main renewable energy source identified to promote energy sustainability in each project. As result, the combination of the six works creates a powerful tool to demonstrate possible best practices for remote mountain areas.